2017
DOI: 10.1111/nmo.13100
|View full text |Cite
|
Sign up to set email alerts
|

The anatomy and physiology of normal and abnormal swallowing in oropharyngeal dysphagia

Abstract: Problems affecting any point along the complex swallowing pathway can result in dysphagia. This review focuses on the anatomy and physiology behind normal and abnormal oropharyngeal swallowing. It also details the common diseases and pathology causing oropharyngeal dysphagia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
160
0
13

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 163 publications
(173 citation statements)
references
References 120 publications
(224 reference statements)
0
160
0
13
Order By: Relevance
“…During the process of eating, food must be masticated, formed into a bolus, and transported into the pharynx, primarily driven by the tongue . Fluids require initial containment and positioning of the ingested fluid in the oral cavity before its subsequent aboral propulsion into the pharynx . During this initial phase of swallowing, lip closure ensures bolus containment in the oral cavity, while cyclic tongue movements, coordinated with jaw movements, process solid foods.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…During the process of eating, food must be masticated, formed into a bolus, and transported into the pharynx, primarily driven by the tongue . Fluids require initial containment and positioning of the ingested fluid in the oral cavity before its subsequent aboral propulsion into the pharynx . During this initial phase of swallowing, lip closure ensures bolus containment in the oral cavity, while cyclic tongue movements, coordinated with jaw movements, process solid foods.…”
mentioning
confidence: 99%
“…Next, the pharyngeal component of swallowing will be initiated by stimulation of the superior laryngeal nerve, a branch of the cranial vagus nerve. This involuntary stage of swallowing is more reflexive …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Swallowing MEP studies have been performed in various ways, including submental MEP using the mylohyoid muscle, pharyngeal MEP, and esophageal MEP . We focused on the mylohyoid muscle, which is the first muscle activated in the automatic phase in oropharyngeal swallowing . After its activation, the muscle contraction and relaxation sequence pushes out the bolus toward the upper esophageal sphincter (UES).…”
Section: Introductionmentioning
confidence: 99%
“…17 We focused on the mylohyoid muscle, which is the first muscle activated in the automatic phase in oropharyngeal swallowing. 18 After its activation, the muscle contraction and relaxation sequence pushes out the bolus toward the upper esophageal sphincter (UES). A previous study by Gallas et al 15 reported that mylohyoid motor evoked potentials (MH-MEP) was associated with the severity of dysphagia in chronic stroke patients.…”
mentioning
confidence: 99%